MORPHOLOGY IN SPEECH STUDENTS OF AL-MAKSUM PRIVATE IT MIDDLE SCHOOL - Ifan Iskandar (JALC : JOURNAL OF APPLIED LINGUISTIC AND STUDIES OF CULTURAL, 2023)
This study aims to describe the types of connection errors, types of repetition errors and types of compound errors in the speech of grade VII students at Al-Maksum private information technology college. This study uses a qualitative descriptive research design with the research subjects being grade VII students at Al-Maksum private IT college. The subject of this study concerns morphological errors in students' speech. Data were collected using audio recording method. Data analysis is performed by transcribing data, arranging, collating, presenting, and drawing conclusions. The results showed that there were 62 arrangement errors, 46 repetition errors and no layout errors.